Study of female entrepreneurship: an empirical evidence in the Municipality of León in Nicaragua - Justa Pastora Amador-Ruiz; Antonio Juan Briones-Peñalver (Tourism & Management Studies)
Women's entrepreneurship is one of the main challenges in economic growth. In this sense, within the context of creating new companies, it can be considered as one of the main mechanisms that contributes to achieve the desired wellbeing in society. Women's entrepreneurship reduces unemployment, increases innovation, improves competitiveness and favors economic growth significantly. This article aims to analyze the influence of the socioeconomic and psychosocial factors involved in female entrepreneurship. For this purpose, we used a sample of 101 women entrepreneurs in the municipality of León, Nicaragua. We applied Factor Analysis and Regression Analysis, in order to find out the relationship between the considered factors. Some results indicate that all variables considered have a significant influence on the probability of entrepreneurship. The capacity of entrepreneurial women increases when they have skills, knowledge and an early contact in the business world